Effects of temperature and hypercapnia on ventilation and breathing pattern in the lizard Uromastyx aegyptius microlepis - Klein, W.; Andrade, D. V. [UNESP]; Wang, T.; Taylor, E. W. (Elsevier B.V., 2002)
In most reptiles, the ventilatory response to hypercapnia consists of large increases in tidal volume (V-T), whereas the effects on breathing frequency (f(R)) are more variable. The increased V-T seems to arise from direct inhibition of pulmonary stretch receptors. Most reptiles also exhibit a transitory increase in ventilation upon removal of CO2 and this post-hypercapnic hyperpnea may consist of changes in both V-T and f(R). While it is well established that increased body temperature augments the ventilatory response to hypercapnia, the effects of temperature on the post-hypercapnic hyperpnea is less described. In the present study, we characterise the ventilatory response of the agamid lizard Uromastyx aegyptius to hypercapnia and upon the return to air at 25 and 35 degreesC. At both temperatures, hypercapnia caused large increases in V-T and small reductions in f(R), that were most pronounced at the higher temperature. The post-hypercapnic hyperpnea, which mainly consisted of increased fR, was numerically larger at 35 compared to 25 degreesC. However, when expressed as a proportion of the levels of ventilation reached during steady-state hypercapnia, the post-hypercapnic hyperpnea was largest at 25 degreesC. Some individuals exhibited buccal pumping where each expiratory thoracic breath was followed by numerous small forced inhalations caused by contractions of the buccal cavity. This breathing pattern was most pronounced during severe hypercapnia and particularly evident during the post-hypercapnic hyperpnea. (C) 2002 Published by Elsevier B.V.
Keywords: hypercapnia; post-hypercapnic hyperpnea; breathing pattern; temperature; buccal pumping; reptile; Uromastyx; ventilatory control